THE GRIEVING RESPONSE OF CERVICAL CANCER PATIENTS IN A REFERRAL HOSPITAL IN BANDUNG CITY - Algia Nuruliani; Aat Sriati; Yanti Hermayanti (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
The grief response could affect the treatment process and the condition of cervical cancer patients which directly gives impact on the patients quality of life. The medical practisers are responsible for helping the patients to pass through the grief process to prevent the adverse effects for the patients, thus it is necessary to know the condition of grief response as the data to analyze the problems and to plan the nursing interventions. This study purpose was to identify the grief response in cervical cancer patients at central hospital Dr. Hasan Sadikin Bandung. The research design was a quantitative descriptive by used the questionary of Preparatory Grief in Advanced Cancer Patients (PGAC) with the validity value of 0.823-0.864 and the reliability value of 0.83. The research sample was the patients of cervical cancer with the total number of 50 persons. The technique of sample selection used an Accidental Sampling carried out in the period of two weeks. The research result from 50 patients showed that most respondents (76%) had low grief and a small number of patients (24%) had severe grief which required further intervention. A big number of respondents (60%) had prolonged grief. The grief responses which mostly existed were the response of emotional sadness (58%), meanwhile, the lowest response was religious comfort response (16%). Although the majority of respondents experienced low grief response, there are still existed severe grief response and also experienced prolonged grief. The high response of sadness showed all the patients of cervical cancer needed emotional and spiritual support as the efforts to prevent the low grief become severe grief response and also to overcome the severe grief and it not to be the prolonged grief.Keywords : Cervical cancer, grief response, preparatory grief.